Phylogeography of the Arizona hairy scorpion (Hadrurus arizonensis) supports a model of biotic assembly in the Mojave Desert and adds a new Pleistocene refugium. (30th January 2013) - Graham, Matthew R.; Jaeger, Jef R.; Prendini, Lorenzo; Riddle, Brett R.; McGeoch, Melodie
Abstract Aim As data accumulate, a multi‐taxon biogeographical synthesis of the Mojave Desert is beginning to emerge. The initial synthesis, which we call the 'Mojave Assembly Model', was predominantly based on comparisons of phylogeographical patterns from vertebrate taxa. We tested the predictions of this model by examining the phylogeographical history of Hadrurus arizonensis, a large scorpion from the Mojave and Sonoran deserts. Location Mojave and Sonoran deserts, United States and Mexico. Methods We sequenced mitochondrial cytochrome c oxidase subunit I (COI) data from 256 samples collected throughout the range of H. arizonensis. We analysed sequence data using a network analysis, spatial analysis of molecular variance (SAMOVA), and a Mantel test. We then used a molecular clock to place the genetic patterns in a temporal framework. We tested for signals of expansion using neutrality tests, mismatch distributions and Bayesian skyline plots. We used Maxent to develop current and late‐glacial species distribution models from occurrence records and bioclimatic variables. Results Phylogenetic and structure analyses split the maternal genealogy basally into a southern clade along the coast of Sonora and a northern clade that includes six lineages distributed in the Mojave Desert and northern Sonoran Desert. Molecular dating suggested that the main clades diverged between the late Pliocene and early Pleistocene, whereas subsequent divergences between lineages occurred in the middle and late Pleistocene. Species distribution models predicted that the distribution of suitable climate was reduced and fragmented during the Last Glacial Maximum. Main conclusions Genetic analyses and species distribution modelling suggest that the genetic diversity within H. arizonensis was predominantly structured by Pleistocene climate cycles. These results are generally consistent with the predictions of Pleistocene refugia for arid‐adapted taxa described in the Mojave Assembly Model, but suggest that a northern area of the Lower Colorado River Valley may have acted as an additional refugium during Pleistocene glacial cycles.